(untitled) (Research Journal, 2024)
The decline of English majors in universities around the world today reflects broader shifts in educational priorities and cultural values. The higher education in Nepal also mirrors the same. This paper examines whether English Major is less coherent as a subject and discipline and scholarly pursuit and explores the factors contributing to the gradual erosion of English programs within both educational institutions and humanities Faculty. Adopting semi-structured interview with some English teachers and Professors at home and abroad as FGD, this study explores the situation of less enrollment in Humanities at plus two levels, misplaced priorities, economic pressures, global exposure and networking opportunities, the emphasis on other disciplines like Science, Engineering, Technology and business fields, and cultural changes in engagement with literature, while considering the implications of English Majors for academia, professional sectors, and communities. This research explores why fewer English Majors in both global and local contexts and highlights the need for interdisciplinary strategies, revising the existing policies and pedagogical strategies, instrumental motivation on both teachers and learners, eco-pedagogy and the revitalization and preservation of the Humanities to maintain cultural and intellectual diversity.